Peran Konselor dan Pekerja Sosial di Panti Rehabilitasi Fokus - Oktavia Naibaho, Yolanda; Dhea Oktaviani Rauna Sitompul, Esica; Letare Winroriauli Sinaga, Hanna; Margretha Zebua, Joice (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
Counselors and social workers play a crucial role in the rehabilitation process, although they have slightly different focuses. Counselors tend to cater to more mature clients, while social workers are more experienced in working with adolescent or emerging adults. Both use assessment tools such as ASSIST, ASI, and Yurika to assess the resident's condition and progress. This study aims to analyze the roles of counselors and social workers at Focus Rehabilitation Center. The methods used include interviews and observation as the main tools for collecting data. Interviews were conducted to understand counselors' perspectives on approaches and challenges in their work, while observations provided a first-hand account of counselors' interactions with residents and their therapeutic processes. The results of this study are expected to provide an in-depth insight into the effectiveness of the role of counselors and social workers in supporting the recovery process of residents from drug dependence at the rehabilitation center.